Iot Optimization in Marine Weather Monitoring for Maritime Activities with Mamdani Fuzzy Analysis Method - Amir Ardika Cahya Riyatna; Iman Fahruzi (Jurusan Teknik Elektro Universitas Trunojoyo Madura, 2025)
Fishermen's activities are highly dependent on weather information. Wind speed, temperature and humidity are important to know so that fishermen can prepare their needs when they want to sail. This research focuses on fishermen and coast guards as the main users to know the condition of the beach. This system uses BME280 sensors to determine air temperature and humidity, while wind speed is obtained from an anemometer sensor. The sensor readings are then sent to the IoT server via the MQTT protocol. Optimization of the IoT system is carried out using fuzzy methods so that the performance results based on the Mean absolute deviation (MAD) value of 0.012236364 and Mean Absolute Percentage Error (MAPE) 0.0258583%. The developed system is able to provide information needed by fishermen and coast guards in providing early warning based on environmental parameters so that it can be used to support decision making related to weather conditions.